2022
DOI: 10.3390/ijms23116311
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer and Anti-Metastatic Role of Thymoquinone: Regulation of Oncogenic Signaling Cascades by Thymoquinone

Abstract: Cancer is a life-threatening and multifaceted disease. Pioneering research works in the past three decades have mechanistically disentangled intertwined signaling networks which play contributory roles in carcinogenesis and metastasis. Phenomenal strides have been made in leveraging our scientific knowledge altogether to a new level of maturity. Rapidly accumulating wealth of information has underlined a myriad of transduction cascades which can be pharmaceutically exploited for cancer prevention/inhibition. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…Chen et al showed that thymoquinone inhibited oxidative stress, inflammatory response, and apoptosis through the p13K/Akt pathway [ 27 ] in MCF-7 cells, and thymoquinone increased ROS levels, leading to greater phosphorylation of p38-MAPK. When p38-MAPK was silenced, the ability of thymoquinone to induce apoptosis in cancer cells was diminished [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al showed that thymoquinone inhibited oxidative stress, inflammatory response, and apoptosis through the p13K/Akt pathway [ 27 ] in MCF-7 cells, and thymoquinone increased ROS levels, leading to greater phosphorylation of p38-MAPK. When p38-MAPK was silenced, the ability of thymoquinone to induce apoptosis in cancer cells was diminished [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of these signaling pathways in the development and progression of CRC has been widely reported in the literature [95,[104][105][106]. The results from recent studies indicate that these elements may be potential targets for TQ [107].…”
Section: Thymoquinone a Promising Candidate For The Treatment Of Colo...mentioning
confidence: 91%
“…TQ is a strong antioxidant that inhibits inflammatory mediators and cancer cells from proliferation [34] and has wound healing action [35].…”
Section: Thymoquinone (Tq)mentioning
confidence: 99%